ADVERSITY QUOTIENT, KNOWLEDGE, AND PROACTIVE PERSONALITY: KEY DETERMINANTS OF WOMEN'S ENTREPRENEURIAL INTENTION - Rika Kristina; Boedi Hartadi Kuslina (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to identify the factors influencing entrepreneurial intention among women in Bandung City, focusing on adversity quotient, entrepreneurial knowledge, and proactive personality. The research method used is quantitative with a causal explanatory approach. Data were collected through a survey technique using a questionnaire designed with a Likert scale. The population of this study consists of adult women in Bandung City, with a sample size of 160 women selected using purposive sampling. The data obtained were analyzed using linear regression to test the influence of independent variables on entrepreneurial intention. The results of the study indicate that adversity quotient has a significant impact on women's entrepreneurial intention. Women with high adversity quotient are more resilient and able to overcome challenges. Entrepreneurial knowledge was also found to have a significant effect. Additionally, proactive personality significantly contributes to entrepreneurial intention. The last but not least, all the variables are influence entrepreneurial intentions simultaneously. These findings suggest that to increase women's participation in entrepreneurship, training programs should include the development of emotional intelligence, intensive entrepreneurship education, and the cultivation of a proactive personality. This research is expected to provide valuable insights for policymakers and entrepreneurship educators in designing more effective programs to encourage women to engage in entrepreneurship.